PENGARUH MODEL EXAMPLE NON_EXAMPLE (ENE) DAN INSIDE OUTSIDE CIRCLE (IOC) DALAM PEMBELAJARAN BERBANTUAN MEDIA AUDIOVISUAL - Muchamat Saiful (Universitas Muria Kudus, 2019)
This study aims to describe the influence of exampel non_example and inside outside circle learning models in thematic learning assisted by audiovisual media of IVSD 2 grade students Temulus, 3 Temulus and 3 Kirig Mejobo Kudus on the sub-theme 1 ethnic diversity and religion in my country in Indonesian and Science. The research method used is experimentation. The design used in experimental research using the design